Implementasi Pembelajaran Proyek Kewirausahaan Mahasiswa Dengan Usaha Kuliner Pisang Goreng Krispy - Ahken Kelvin Sampe Angin; Sepryanto Fernandus D; Leris Pasuang; Ariel Syahputra Tandi Pasang; Arthur C Bida; Rachmasari Pramita Wardhani; Lukman (JURNAL TEKNOSAINS KODEPENA, 2026)
The purpose of the applied practicum is to foster independence and train students' skills in designing and running a business, as well as understanding business analysis. The activity begins with students creating a business plan project and implementing it. One of the business ideas being pursued is the culinary industry, with the aim of highlighting the potential of local products that are readily available, affordable, and popular with the community. The research method used is a mixed-methods approach with an applied approach, with the implementation of the business practice activities. The applied project learning from the entrepreneurship course practical activities is expected to foster independence and an entrepreneurial spirit, as well as train students in designing and running a business. This education is beneficial. This entrepreneurship project activity serves as an educational platform for students, motivating them to apply concepts from business management, production processes, and product innovation in real life. Keywords: Implementation, Project Learning, Entrepreneurship, Culinary